2020
DOI: 10.1016/j.heliyon.2020.e03602
|View full text |Cite
|
Sign up to set email alerts
|

Low-cost fabrication of optical tissue phantoms for use in biomedical imaging

Abstract: The rapid development of new optical imaging techniques is dependent on the availability of low-cost and easily reproducible standards for technique validation. This work describes a low-cost fabrication process of an agar gelbased phantom that may accurately simulate the optical properties of different human tissues at 532 and 630nm wavelengths. It was designed to match the optical properties of the brain, bladder wall, and lung tissues. These low-cost phantoms use agar powders dissolved in water as the bulk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…It is sometimes desired that phantoms also have acoustic and optical properties that match the specific tissue to be mimicked, which can be particularly important for use with certain imaging modalities and applications such as quality control. 4,5,41 Multiple studies have reported the use of various additives and scattering materials to tissuemimicking materials in order to control the acoustic and optical properties. 8,37,39 A study by Alves et al utilizing the same tissue-mimicking gel combined with mineral oil and cellulose powder reported acoustic properties within the range of cardiac tissue and standards for phantoms.…”
Section: Discussionmentioning
confidence: 99%
“…It is sometimes desired that phantoms also have acoustic and optical properties that match the specific tissue to be mimicked, which can be particularly important for use with certain imaging modalities and applications such as quality control. 4,5,41 Multiple studies have reported the use of various additives and scattering materials to tissuemimicking materials in order to control the acoustic and optical properties. 8,37,39 A study by Alves et al utilizing the same tissue-mimicking gel combined with mineral oil and cellulose powder reported acoustic properties within the range of cardiac tissue and standards for phantoms.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome this challenge, we placed a polydimethylstyrene (PDMS) phantom with a high concentration of polystyrene beads with a well-characterized scattering profile to serve as an additional scattering layer over the sample. 22,23 We simulated the illumination distribution of the system using the optical properties of the PDMS phantom. To capture the dynamic information, cells were imaged continuously at 4 or 32 frames per second (fps) over 1 or 8 min, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The hair thickness varies between 56 and 99 μm. Imaging of the suspended samples was done in three variations: in air (with OCT only), in deionized water and in agar phantom, which is often used as tissue‐mimicking phantoms for ultrasound and photoacoustic imaging [35–37].…”
Section: Methodsmentioning
confidence: 99%